THE ARTISTIC ORIGINALITY OF L. PETRUSHEVSKAYA’S CREATIVITY - Fayziyeva S.A.; Jafarova Dilnoza (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: Petrushevskaya’s work is a special, in many ways unique artistic world. The artistic world of Lyudmila Petrushevskaya is a complex synthesis of mutually exclusive aesthetic trends: postmodernism and realism, naturalism and sentimentalism, modernism and baroque. The genre diversity of her works is quite large. These include dramatic and prose works, as well as fairy-tale prose.